School Principals’ Evaluation of the Effectiveness of Employing Distance Learning Tools by Teachers - Abukhalil, Thaer A.R.; Halawani, Shaima M-F.; Daher, Wajeeh M. (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The study examined the criterions that school principals used to evaluate the effectiveness of the use of distance learning tools in the COVID-19 pandemic by school teachers. Six school administrators were interviewed regarding their evaluation of the technological tools used by the teachers in distance. The constant comparative method was used to analyze the interview data. The study results indicated ten criterions that served the principals in their evaluation:(1) Availability of the technological tool in students’ hands, (2) The teacher’s ability to handle the tool used, (3) The fit of the used tool to the specific content, (4) The fit of the used tool to the curriculum objectives, (5) Planning the use of the tool in the classroom, (6) Use of technological tools for interactive communication in the classroom, (7)Use of technological tools to stimulate, attract and engage students in distance learning, (8) Use of technological tools to achieve quality education, (9) Use of technological tools to manage students’ behavior in distance learning, and (10) Using mobile tools to encourage students’ engagement in distance learning. More research is needed to study school principals’ behavior regarding E-learning especially in emergency education.